Exploring the role of mindfulness in the stress-recovery balance: 10-Day monitoring of young BMX riders in an intensive training center during a pre-competition cycle - Sondt, N.; Bernier, M.; Kermarrec, G.; Vacher, P. (Psychology of Sport and Exercise, 2024)
Considering mindfulness as a multidimensional disposition domain-specific skill and state, this study aimed to explore the effect of the dimensions of mindfulness on the trajectories of biopsychosocial stress-recovery balance and on HRV over 10 days of a pre-competitive cycle. 24 young BMX riders completed mindfulness disposition and domain-specific skill scales. Monitoring of the recovery-stress states was based on biopsychosocial measurements (daily and biweekly). RMSSD was used to assess the organism ability to cope with the training program stimulus. After each training session, riders self-rated their state of mindfulness. Multilevel growth curve analyses examined the linear and/or quadratic trajectories of the athletes` recovery-stress states and the effect of mindfulness on these trajectories. Mindfulness states results showed that the refocusing state had a significant negative quadratic effect over time on daily recovery and sport-specific recovery, and the awareness state on general recovery and total recovery. Concerning the dispositions of mindfulness, the observing component had a significant positive quadratic effect over time on daily stress. Nonreactivity had a significant positive quadratic effect over time on daily recovery and sport-specific recovery, and a significant positive effect on RMSSD. Acting with awareness had a significant positive effect on daily recovery and a significant negative effect on RMSSD. The study offered a better understanding of the effect of mindfulness (dispositions, domain-specific skills, and states) and its different components on the stress-recovery balance. The results suggest that mindfulness could be considered a promising effective psychological recovery strategy.